Understanding Behavioral Transformation of Resuscitative Subjects - Raghavendra Prasad, G. (International Journal of Psychosocial Rehabilitation, 2024)
Near Death Experience, it has been still a debatable phenomenon after so many research works done across theworld. The scientific community is still harping about the phenomena and there is an extreme urge to unveil therelation of human behaviour with brain in cognitive resurgence occurring after the phenomena. There is alsoanexistential impulse to associate the relation between the cognitive restructuring, behavioural change and NearDeath Experience (NDE). The post recovery phases usually quoted as Post Traumatic Stress Disorder (PTSD)generally indicates the negative impact caused by phenomenon like NDE. In an attempt to understand the actualaftermath and the relation between behavioural change and NDE, the author is proposing a NDE- Mixed-MethodDesign Protocol (NMDP). The protocol will be helpful in understanding and establishing the cognitive resurrectionhappening in the brains of NDErs and the repercussion of the phenomenon through a combination of Qualitativeand Quantitativeresearch techniques